PENGARUH REPUTASI AUDITOR DAN UKURAN PERUSAHAAN PADA KEAKURATAN DALAM PEMBERIAN OPINI GOING CONCERN - Kemuning, Ni Luh Dea; Juliarsa, Gede (E-Jurnal Akuntansi, 2016)
1024x768 This research was conducted to fulfill the purpose of obtaining empirical evidences on whether auditor’s reputation and company size affected the granting of going concern opinion accuracy. The accuracy of going concern opinion was proxied through company’s bankruptcy after receiving going concern opinion, that if the company goes bankrupt after receiving going concern opinion, the granting of going concern opinion is considered accurate. Samples obtained through purposive sampling method were 42 manufacturing companies listed on Indonesia Stock Exchange throughout 2004-2008 period. Data analysis technique and hypothesis test performed with logistic regression analysis . The findings indicated that auditor’s reputation affected the granting of going concern opinion accuracy, while company size didn’t affect the granting of going concern opinion accuracy. The higher the reputation, the more accurate the granting of going concern opinion accuracy would be. Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} table.MsoTableColorfulListAccent1 {mso-style-name:"Colorful List - Accent 1"; mso-tstyle-rowband-size:1; mso-tstyle-colband-size:1; mso-style-priority:34; mso-style-unhide:no; mso-style-link:"Colorful List - Accent 1 Char"; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-tstyle-shading:#EDF2F8; mso-tstyle-shading-themecolor:accent1; mso-tstyle-shading-themetint:25; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; color:black; mso-themecolor:text1;} table.MsoTableColorfulListAccent1FirstRow {mso-style-name:"Colorful List - Accent 1"; mso-table-condition:first-row; mso-style-priority:34; mso-style-unhide:no; mso-style-link:"Colorful List - Accent 1 Char"; mso-tstyle-shading:#9E3A38; mso-tstyle-shading-themecolor:accent2; mso-tstyle-shading-themeshade:204; mso-tstyle-border-bottom:1.5pt solid white; mso-tstyle-border-bottom-themecolor:background1; color:white; mso-themecolor:background1; mso-ansi-font-weight:bold; mso-bidi-font-weight:bold;} table.MsoTableColorfulListAccent1LastRow {mso-style-name:"Colorful List - Accent 1"; mso-table-condition:last-row; mso-style-priority:34; mso-style-unhide:no; mso-style-link:"Colorful List - Accent 1 Char"; mso-tstyle-shading:white; mso-tstyle-shading-themecolor:background1; mso-tstyle-border-top:1.5pt solid black; mso-tstyle-border-top-themecolor:text1; color:#9E3A38; mso-themecolor:accent2; mso-themeshade:204; mso-ansi-font-weight:bold; mso-bidi-font-weight:bold;} table.MsoTableColorfulListAccent1FirstCol {mso-style-name:"Colorful List - Accent 1"; mso-table-condition:first-column; mso-style-priority:34; mso-style-unhide:no; mso-style-link:"Colorful List - Accent 1 Char"; mso-ansi-font-weight:bold; mso-bidi-font-weight:bold;} table.MsoTableColorfulListAccent1LastCol {mso-style-name:"Colorful List - Accent 1"; mso-table-condition:last-column; mso-style-priority:34; mso-style-unhide:no; mso-style-link:"Colorful List - Accent 1 Char"; mso-ansi-font-weight:bold; mso-bidi-font-weight:bold;} table.MsoTableColorfulListAccent1OddColumn {mso-style-name:"Colorful List - Accent 1"; mso-table-condition:odd-column; mso-style-priority:34; mso-style-unhide:no; mso-style-link:"Colorful List - Accent 1 Char"; mso-tstyle-shading:#D3DFEE; mso-tstyle-shading-themecolor:accent1; mso-tstyle-shading-themetint:63; mso-tstyle-border-top:cell-none; mso-tstyle-border-left:cell-none; mso-tstyle-border-bottom:cell-none; mso-tstyle-border-right:cell-none; mso-tstyle-border-insideh:cell-none; mso-tstyle-border-insidev:cell-none;} table.MsoTableColorfulListAccent1OddRow {mso-style-name:"Colorful List - Accent 1"; mso-table-condition:odd-row; mso-style-priority:34; mso-style-unhide:no; mso-style-link:"Colorful List - Accent 1 Char"; mso-tstyle-shading:#DBE5F1; mso-tstyle-shading-themecolor:accent1; mso-tstyle-shading-themetint:51;}
Keywords: Going Concern Opinion, Auditor’s Reputation, Company Size, Financial Distress, Type I Reporting Error